2017
DOI: 10.9758/cpn.2017.15.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Alzheimer’s Disease Pathogenesis and Prevention: The Brain, Neural Pathology, N-methyl-D-aspartate Receptors, Tau Protein and Other Risk Factors

Abstract: The characteristic features of Alzheimer’s disease (AD) are the appearance of extracellular amyloid-beta (Aβ) plaques and neurofibrillary tangles in the intracellular environment, neuronal death and the loss of synapses, all of which contribute to cognitive decline in a progressive manner. A number of hypotheses have been advanced to explain AD. Abnormal tau phosphorylation may contribute to the formation of abnormal neurofibrillary structures. Many different structures are susceptible to AD, including the ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
102
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(115 citation statements)
references
References 120 publications
(114 reference statements)
1
102
0
6
Order By: Relevance
“…Tau is one of the most widely studied MAPs due to its association with neurological diseases such as frontotemporal dementia (FTD) and Alzheimer's disease (AD) (Tolnay and Probst, 1999;Del Carmen Alonso, 2010;Irwin et al, 2013;Ghetti et al, 2015;Gao et al, 2017;Kocahan and Dogan, 2017). Tau is now also a marker of brain damage following traumatic brain injury (TBI) (Zemlan et al, 1999;Zemlan et al, 2002;Franz et al, 2003;Smith et al, 2003;Tran et al, 2011a;Tran et al, 2011b;Hawkins et al, 2013;Kondo et al, 2015), highlighting the deleterious role of tau in neurodegeneration.…”
Section: Taumentioning
confidence: 99%
“…Tau is one of the most widely studied MAPs due to its association with neurological diseases such as frontotemporal dementia (FTD) and Alzheimer's disease (AD) (Tolnay and Probst, 1999;Del Carmen Alonso, 2010;Irwin et al, 2013;Ghetti et al, 2015;Gao et al, 2017;Kocahan and Dogan, 2017). Tau is now also a marker of brain damage following traumatic brain injury (TBI) (Zemlan et al, 1999;Zemlan et al, 2002;Franz et al, 2003;Smith et al, 2003;Tran et al, 2011a;Tran et al, 2011b;Hawkins et al, 2013;Kondo et al, 2015), highlighting the deleterious role of tau in neurodegeneration.…”
Section: Taumentioning
confidence: 99%
“…Among those tracts, cingulum showed overall the best diagnostic performance as a single tract, similar to previous TRACULAR study of aMCI and AD. 41) The cingulum is known as a tract contains efferent fiber from entorhinalhippocampal complex, 43) seems to reflect early alteration of aMCI patients. 44) In this study, we showed that combined FA and MD values of memory related tracts showed high diagnostic accuracy in both of FA and MD with 0.98, 0.95 of AUC respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's disease (AD), a well-known neurodegenerative disorder that acts chronically and incurably, is the most common style of dementia and characterized by the appearance of extracellular amyloid-β (Aβ) plaques and neurofibrillary tangles in the intracellular environment, neuronal death, and the loss of synapses, all of which contribute to cognitive decline in a progressive manner. 1 The Aβ-amyloid hypothesis is currently the best-developed mechanism to explain AD pathogenesis; however, quite a number of researches have suggested the weak correlation between Aβ deposition and neuronal atrophy and cognitive impairment. 2,3 Several studies revealed epigenetic DNA methylation and hydroxymethylation could be involved in the pathogenesis of AD and probably play a crucial role in regulating gene expression involved in multiple neurodevelopmental and neurodegenerative disorders.…”
Section: Introductionmentioning
confidence: 99%